The Columbia guide to American Indians of the Southeast - Perdue, Theda, 1949-; Green, Michael D., 1941-2013 (Columbia guides to American Indian history and culture., 2001)
Though they speak several different languages and organize themselves into many distinct tribes, the Native American peoples of the Southeast share a complex ancient culture and a tumultuous history. This volume examines and synthesizes their history through each of its integral phases: the complex and elaborate societies that emerged and flourished in the Pre-Columbian period; the triple curse of disease, economic dependency, and political instability brought by the European invasion; the role of Native Americans in the inter-colonial struggles for control of the region; the removal of t.